Total laparoscopic hysterectomy with obliterated anterior cul-de-sac - Walid, M. Sami; Heaton, Richard L. (GMS German Medical Science, 2010)
Endometriosis may in severe cases lead to obliteration of the anterior and/or posterior cul-de-sacs in the female pelvis. The anterior cul-de-sac is generally less commonly affected. This type of cases usually presents a challenge for the operating surgeon, whether via open route or through laparoscopy. In this paper, we present an illustrative case and explain our technique for dealing with a scarred and totally obliterated anterior cul-de-sac because of endometriosis during total laparoscopic hysterectomy.